Tyrosinase Activated Melanoma Prodrugs - Jawaid, Samaila; Khan, Tariq H.; Osborn, Helen M.I.; Williams, Nana Aba O. (Anti-Cancer Agents in Medicinal Chemistry, 2009)
Metastatic malignant melanoma remains a highly aggressive form of skin cancer for which no reliable methods for treatment exist. Given the increasing incidence of this cancer, considerable attention has focused on the development of new and improved methods for tackling this disease. Within this article, methods for treating melanoma are reviewed and discussed with particular attention focusing on prodrugs that are activated by the tyrosinase enzyme. This enzyme is up-regulated and is of elevated activity within malignant melanomas compared with healthy melanocytes, providing an ideal in-situ tool for the activation of melanoma prodrugs. By way of background to the prodrug strategies discussed within this review, the causes of melanoma, the enzymology of tyrosinase, and the chemistry of the biosynthetic pathways associated with melanogenesis are presented. Aspects of the design, mode of action, and biological profiles of key prodrugs that are activated by tyrosinase, and that show potential for the treatment of melanoma, are then presented and compared.
Keywords: metastasis